(untitled) (Research, Society and Development, 2024)
The initial bond between mother and child is characterized by an intense emotional exchange, which involves both the pleasure of motherhood and the anguish generated by the care demands. The general objective of this study is to analyze the mother-baby bond from a psychoanalytic perspective, focusing on the interaction between anguish and pleasure, to understand how these elements influence the emotional and psychological development of both mother and baby. This literature review study explores the complex bond between mother and baby, analyzing the emotional dynamics that permeate this relationship from a psychoanalytic perspective. Reviewing the research of psychoanalytic theorists allows us to understand how these feelings coexist and impact the emotional development of the baby and mother. The analysis of the stages of child development and the defense mechanisms used by the mother contributes to a deeper understanding of this dilemma. The study reveals the importance of recognizing and dealing with the ambivalence of maternal feelings, highlighting the implications for the mental health of both mother and child.